Kňiha pamňetni Tomše Hrůzy, žitele Vojvodofského - Jakoubek, Marek (Lidé města, 2010)
The publication presents a commented transliteration of the notes (“Book of Memorials”) written by Tomeš Hrůza, an inhabitant of Vojvodovo, a Czech village in Bulgaria. The notes cover many aspects of the history and the life of Vojvodovo Czech villagers; the main focus is, however, on the economic situation in the period of 1929-44. The edition is supplemented by informative commentaries and prefaced by a short introduction explaining the background of the manuscript in the context of the history of Vojvodovo and its former Czech inhabitants.